모의 산후 우울과 아동의 사회정서 발달과의 관계 - 송선영; Sun Young Song; 김광웅; Kwang Woong Kim (한국놀이치료학회지(놀이치료연구), 2000)
This study has the purpose of examining the degrees of depression after child birth and the factors concerning a postpartum depression, and the relationship between a postpartum de-pression and the social emotion development of her child. The subjects of this study are 2, 3,4, and 5 year-old children and their mothers in 8 kindergartens in Seoul, Inchon and Kyunggi district. The results of this examination are as follows. First, the postpartum depression degrees are different in the factors concerning a postpartum depression Second, the mother`s depression has an influence eel the child`s self-control factors and its achievement motives, The damage to the perception of self-identity is an influential factor in explaining the factors concerning relationship with other children.